Extending the post‐thaw viability of cryoprecipitate. Issue 5 (17th March 2021) - Thomson, Candice; Sobieraj‐Teague, Magdalena; Scott, Darren; Duncan, Elizabeth; Abraham, Sunil; Roxby, David
Abstract: Background: Cryoprecipitate has a short post‐thaw expiry time of 6 h. The aim of this study was to assess the stability and function of cryoprecipitate components (FVIII, fibrinogen, vWF, and FXIII) and cryoprecipitate sterility up to 120 h post‐thawing when stored at two temperatures (2–6°C and room temperature [20–24°C]). Methods and Materials: Twenty batches (110 individual units) of time‐expired, thawed cryoprecipitate were collected. Units were sampled at the 6‐h expiration mark and then stored at 2–6°C or room temperature (RT). They were resampled every 24 h for 120 h. One unit from each batch was sent for sterility testing at 120 h. Samples had FVIII (one stage and chromogenic), fibrinogen, FXIII, vWFag, and vWF:RCo assays performed in batches. Rotational thromboelastometry (ROTEM) was also performed. Results: FVIII levels declined significantly at 120 h post‐thawing at both RT and 2–6°C, but still met international standards for FVIII content. Fibrinogen, vWF antigen, and FXIII levels reduced minimally over 120 h and always met international standard requirements when stored at either temperature. ROTEM analysis demonstrated that fibrinogen function was not compromised at 120 h post‐thawing under both storage conditions. vWF:RCo levels declined significantly over 120 h at both storage temperatures. No bacterial contamination was detected in 20 units of cryoprecipitate following storage for 120 h post‐thawing. Conclusion: These results demonstrate that extension of the storage time of thawed cryoprecipitate to 120 h, stored at either 2–6°C or RT, is feasible while still maintaining required FVIII, fibrinogen, and vWFag levels. Storage at 2–6°C has the advantage of reduced risk of potential bacterial contamination.